X-ray baggage object detection using neural networks for safety purposes / Samuel Ato Gyasi Otabir ... [et al.] - Otabir, Samuel Ato Gyasi; Wei, Hong Lim; Sew, Sun Tiang; Hung, Yang Leong; Ang, Chun Kit (College of Built Environment, 2023)
X-rays have been employed to assist in object detection for airport security purpose.